Preparation, Characterization, and Evaluation of Humidity-Dependent Electrical Properties of Undoped and Niobium Oxide-Doped TiO2 : WO3 Mixed Powders - Pedro M. Faia; Juliano Libardi; Itamar Barbosa; Evando S. Araújo; Helinando P. de Oliveira (Advances in Materials Science and Engineering)
The study of selective metal oxide-based binary/ternary systems has received increasing interest in recent years due to the possibility of producing efficient new ceramic materials for relative humidity (RH) detection, given the superior properties of the mixed compounds in comparison with pristine ones. The aim of this work was focused on preparation and characterization of non-doped and Nb2O5-doped TiO2 : WO3 pair (in the pellet form) and evaluation of corresponding humidity-dependent electrical properties. The microstructure of the samples was analyzed from scanning electron microscopy, X-ray diffraction patterns, Raman spectra, BET surface area analysis, and porosimetry. The electrical characterization was obtained from impedance spectroscopy (100 Hz to 40 MHz) in the 10–100% RH range. The results showed that adequate doping levels of Nb2O5 introduce important advantages due to the atomic substitution of Ti by Nb atoms in highly doped structures with different levels of porosity and grain sizes. These aspects introduced a key role in the excursion (one order of magnitude) in the bulk resistance and grain boundary resistance, which characterizes these composite ceramics as a promising platform for RH identification.